(untitled) (International Conference on Computers in Education, 2017)
Learning English has been a global trend since English is widely regarded as an international language for effective communication in the global village where we live today. However, Taiwan is a non-English speaking country; the lack of professional English teachers in Taiwan is still a serious problem both in the countryside and the city. In order to solve this problem, in our study the telexistence robot comes to play. To make teachers feel a sense of telepresence, more feedbacks were prepared for the scene and more focal points for the scene were enriched on teaching scenario. The robot was designed in the newest technological way where virtual reality (VR) and diverse sensors were employed to receive telepresence and feedback. Teachers could become even more engaged in teaching scenarios and operate the robot from a distance through wireless communication technology. The application of telexistence robot has been commonly recognized, and users can operate the robot by sensors whose wireless signal transmits from the user to the robot. The user wears wearable devices on both arms, both feet and the head to control the remote robot to display the same body movement and position. In this way, the application of the telexistence robot to teaching in the elementary school seems practical and feasible. The findings of this study reveal that RALL (Robot Assisted Language Learning) group did make students more motivated and create a more joyful learning environment, compared to the traditional teaching method without RALL.